Biomimetic Approaches Employing the Ugi Five-Center Four-Component Reaction for Synthesis of the Right-Hand Portion of Halichonadin Q and the Central Part of Halichonadin M - Mimura, Rika; Kitamori, Ayumi; Ikeda, Akifumi; Masuda, Toshiya; Nakano, Keiji; Kotsuki, Hiyoshizo; Ichikawa, Yoshiyasu (Synthesis, 2015)
One-pot syntheses of models of the right-hand portion and the central part of the respective structures of halichonadins Q and M, using the Ugi five-center four-component reaction (U-5C-4CR), were executed. The biomimetic strategy employed in these routes demonstrates the feasibility of pathways we have proposed for the biosynthesis of marine organisms.
Keywords: Ugi reaction; multicomponent reaction; biomimetic synthesis; terpenes; isocyanides